As representações dos ciganos no cinema: documentário brasileiro - Miranda, Francielle Felipe Faria de (2011)
This paper investigates the processes of Roma representations in the Brazilian documentary through the films Escuta, gajon (Alice Lanari, 2008), Diana e Djavan: casamento cigano (Luciana Sampaio, 2007), Tarabatara (Júlia Zakia, 2007) e Ciganos do Nordeste (Olney São Paulo, 1977). Here the study of social representations as a field of study that combines several research arenas, speaks to the cinema and audiovisual in order to understand how Roma images are architected, structured and presented to the public. This study aims to understand the point of view of those who produce and select images using the concept of "voice of the documentary" and identifies cinematic perspectives of these relationships with Brazilian culture and the way as the Roma were represented throughout the history of Brazil.